2016
DOI: 10.1016/j.bbacli.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of estrogen receptor α mRNA in peripheral blood cells are an independent biomarker for postmenopausal osteoporosis

Abstract: BackgroundThe up- and down-regulation of the osteoclastogenesis response depends on the estrogen/estrogen receptor (ER) signaling pathway. Previous reports have shown that the promoter hypermethylation and gene polymorphism of ERα are risks for menopausal osteoporosis. No previous study has evaluated the expression levels of ERα mRNA in menopausal osteoporosis using human subjects. We hypothesized that ERα mRNA expression may show less resistance to postmenopausal osteoporosis.MethodsIn this study, we enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have identified some biomarkers for osteoporosis. However, clinical applications of these biomarkers are limited by either their invasive nature or low diagnostic sensitivity and specificity [ 16 , 17 ]. In the present study, we identified plasma PTCSC3 upregulation in osteoporosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified some biomarkers for osteoporosis. However, clinical applications of these biomarkers are limited by either their invasive nature or low diagnostic sensitivity and specificity [ 16 , 17 ]. In the present study, we identified plasma PTCSC3 upregulation in osteoporosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OP develop reduced BMD and osteolysis, which is related to the imbalance of osteogenic differentiation and adipogenic differentiation in rBMSCs. ERα plays a more important role in OP than ERβ, and exerted bone-protective effects by controlling the activity of osteoblasts and osteoclasts (Chou et al, 2016). The ERα signaling axis also participates in osteoblast maturation (Lin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is an important hormone in the body, which is involved in various activities in many organisms. It is imperative for bone growth, development, and maintenance of bone health in adulthood (Chou, Chiang, Chang, Huang, & Cheng, 2016;Mandourah et al, 2018). Most estrogenic effects are mediated by the nuclear hormone receptor, which comprises estrogen receptor alpha and beta (ERα and ERβ; Novack, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, its antagonistic Wnt signal increases with age [31]. On one hand, the decrease in estrogen will lead to an increase of osteoclasts and osteoclastic activity; on the other hand, it can promote the secretion of inflammatory factors, such as that of the interleukin and tumor necrosis factor (TNF) family, further promoting bone resorption, and affecting the balance of the RANKL-RANK-OPG axis, leading to increased osteoclast differentiation and activation of osteoclastic activity [32]. Rap1 is critical for resorptive function, and its selective inhibition in mature osteoclasts retards pathological bone loss [33].…”
Section: Discussionmentioning
confidence: 99%